2022
DOI: 10.1021/acs.jpcc.1c10132
|View full text |Cite
|
Sign up to set email alerts
|

Photoexcited Electron Dynamics in Cd3As2 Revealed by Time- and Energy-Resolved Photoemission Electron Microscopy

Abstract: Cd 3 As 2 , as a three-dimensional Dirac semimetal, has attracted considerable research interest because of its distinct optoelectronic and topological properties. However, simultaneous studies on the carrier dynamics in Cd 3 As 2 in spatial, temporal, and energy dimensions are still lacking. Here, we apply photoemission electron microscopy combined with the femtosecond pump− probe technique to reveal the dynamics of the Cd 3 As 2 nanoplate. The photoexcited electrons on the Cd 3 As 2 surface decay fast with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…Diverse carrier dynamics in 2D materials with time scales from tens of femtoseconds to hundreds of picoseconds, such as carrier thermalization, cooling, exciton–exciton annihilation, intervalley scattering, valley depolarization, and defect trapping, have been characterized by transient absorption or reflection spectroscopy, time- and angle-resolved photoemission spectroscopy, , time-resolved photoemission electron microscopy (TR-PEEM), etc. Among these techniques, femtosecond TR-PEEM has advantages in probing the ultrafast carrier dynamics with additional ultrahigh spatiotemporal resolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse carrier dynamics in 2D materials with time scales from tens of femtoseconds to hundreds of picoseconds, such as carrier thermalization, cooling, exciton–exciton annihilation, intervalley scattering, valley depolarization, and defect trapping, have been characterized by transient absorption or reflection spectroscopy, time- and angle-resolved photoemission spectroscopy, , time-resolved photoemission electron microscopy (TR-PEEM), etc. Among these techniques, femtosecond TR-PEEM has advantages in probing the ultrafast carrier dynamics with additional ultrahigh spatiotemporal resolution.…”
mentioning
confidence: 99%
“…Among these techniques, femtosecond TR-PEEM has advantages in probing the ultrafast carrier dynamics with additional ultrahigh spatiotemporal resolution. Moreover, time- and energy-resolved photoemission electron microscopy (TR- and ER-PEEM) can reveal the dynamics of excited-state carriers in the energy domain by combining an energy analyzer. ,, TR- and ER-PEEM have been used in revealing the ultrafast carrier dynamics of a number of materials, such as inorganic semiconductors, , graphene, transition metal dichalcogenides, perovskite, , etc. , …”
mentioning
confidence: 99%
“…The three-dimensional Dirac semimetal Cd 3 As 2 , a bulk analog of graphene, has attracted widespread attention because of its ultrahigh carrier mobility and gapless Dirac band structure. Similar to graphene, Cd 3 As 2 can be used in broadband photodetectors with a detection spectrum ranging from ultraviolet to long-wave infrared. , In contrast to monolayer graphene, which has an absorption coefficient of ∼2.3%, the bulk characteristics of Cd 3 As 2 endow it with a strong absorption capability and consequently better photoresponsivity. In addition, similar to graphene, , the Cd 3 As 2 photodetector exhibits an ultrafast response up to the picosecond scale, as revealed by previous femtosecond pump–probe measurements. Meanwhile, the oxidation layer on the surface of Cd 3 As 2 provides good stability through isolation from the external environment . Therefore, Cd 3 As 2 is a promising material for high-performance photodetectors.…”
mentioning
confidence: 71%
“…35,36 The PEEM is a powerful tool for investigating photonic modes, including surface plasmon polaritons, 37,38 dielectric waveguides, 39,40 and QCW modes. 27 In our previous work, 9 we demonstrated that the photoemission intensity of Cd 3 As 2 is proportional to the electric field intensity. The increased electric field contributes to optical absorption.…”
mentioning
confidence: 99%
See 1 more Smart Citation